The Relevance of Hadith and Reason in Demonstrating The Status of Hadith - Idris Siregar; Alwi Padly Harahap (Al-Bukhari : Jurnal Ilmu Hadis, 2024)
If the authenticity of a hadith is uncertain and contradicts reason, then the hadith is considered weak. However, if a hadith is considered authentic by hadith scholars, two different theories emerge among the scholars. The first theory argues that true hadith never contradict reason. According to this view, common sense and clarity will never conflict with authentic hadith. On the other hand, the second theory argues that the Prophet's hadith are considered weak if they conflict with reason. This research uses analytical and library research methods, which utilize various scientific works including books, articles and writings by Muslim scholars. The findings of this research show that when a hadith, which is narrated through a strong chain of narrators and its sanad goes back to the Prophet, cannot contradict reason. However, if a hadith goes against common sense, then that can be a valid reason to question its authenticity and consider it weak. Through comprehensive scientific discourse analysis, this research provides a deeper understanding of the complex relationship between hadith and reason and how Islam values reason. This underscores the importance of a rigorous authentication process, emphasizing the need to consider the reliability of hadith sanads and principles of intellectual reasoning when assessing the strength or weakness of a Prophetic hadith